2016
DOI: 10.1111/jnc.13664
|View full text |Cite
|
Sign up to set email alerts
|

FABP‐1 gene ablation impacts brain endocannabinoid system in male mice

Abstract: Liver fatty acid binding protein (FABP1, L-FABP) has high affinity for and enhances uptake of arachidonic acid (ARA, C20:4, n-6) which, when esterified to phospholipids, is the requisite precursor for synthesis of endocannabinoids (EC) such as arachidonoylethanolamide (AEA) and 2-arachidonoylglycerol (2-AG). The brain derives most of its ARA from plasma, taking up ARA and transporting it intracellularly via cytosolic fatty acid binding proteins (FABPs 3,5, and 7) localized within the brain. In contrast, the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(127 citation statements)
references
References 146 publications
(136 reference statements)
3
123
1
Order By: Relevance
“…Fifth, loss of FABP1 markedly increased ARA-containing endocannabinoid (AEA, 2-AG) levels in liver (shown herein) and brain (13) of male mice. Despite similar endpoint, however, these increases were likely due to somewhat different mechanisms since FABP1 is not found in brain (1113,53).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Fifth, loss of FABP1 markedly increased ARA-containing endocannabinoid (AEA, 2-AG) levels in liver (shown herein) and brain (13) of male mice. Despite similar endpoint, however, these increases were likely due to somewhat different mechanisms since FABP1 is not found in brain (1113,53).…”
Section: Discussionmentioning
confidence: 71%
“…FABP1 bound AEA and 2-AG ≥3-fold more strongly as compared to SCP2 (13). In fact, FABP1 bound AEA and 2-AG with the highest affinity yet reported for any FABP family member.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct comparison of Fabp2 −/− and Fabp1 −/− mice fed high fat diets also suggested that the two enterocyte proteins play different roles in intestinal and systemic metabolism [18]. Recent works indicate that Fabp1 −/− mice shows impaired endocannabinoid system both in liver and in the brain [23,24]. …”
Section: Introductionmentioning
confidence: 99%